Climate Variability : Some Aspects, Challenges and Prospects - Hannachi, Abdel; Hannachi, Abdel (IntechOpen, 2012)
This book provides a general introduction to the popular topic of climate variability. It explores various aspects of climate variability and change from different perspectives, ranging from the basic nature of low-frequency atmospheric variability to the adaptation to climate variability and change. This easy and accessible book can be used by professionals and non professionals alike.
English
Keywords: Climate change; Climate change